Correlates of protection for meningococcal surface protein vaccines: current approaches for the determination of breadth of coverage. (3rd June 2022) - Findlow, Jamie; Borrow, Ray; Stephens, David S.; Liberator, Paul; Anderson, Annaliesa S.; Balmer, Paul; Jodar, Luis
ABSTRACT: Introduction: The two currently licensed surface protein non-capsular meningococcal serogroup B (MenB) vaccines both have the purpose of providing broad coverage against diverse MenB strains. However, the different antigen compositions and approaches used to assess breadth of coverage currently make direct comparisons complex. Areas covered: In the second of two companion papers, we comprehensively review the serology and factors influencing breadth of coverage assessments for two currently licensed MenB vaccines. Expert opinion: Surface protein MenB vaccines were developed using different approaches, resulting in unique formulations and thus their breadth of coverage. The surface proteins used as vaccine antigens can vary among meningococcal strains due to gene presence/absence, sequence diversity, and differences in protein expression. Assessment of the breadth of coverage provided by vaccines is influenced by the ability to induce cross-reactive functional immune responses to sequence diverse protein variants; the characteristics of the circulating invasive strains from specific geographic locations; methodological differences in the immunogenicity assays; differences in human immune responses between individuals; and the maintenance of protective antibody levels over time. Understanding the proportion of meningococcal strains, which are covered by the two licensed vaccines, is important in understanding protection from disease and public health use.